Nickel‐Catalyzed Enantioconvergent Carboxylation Enabled by a Chiral 2, 2′‐Bipyridine Ligand. (22nd November 2022) - Wang, Linghua; Li, Tao; Perveen, Saima; Zhang, Shuai; Wang, Xicheng; Ouyang, Yizhao; Li, Pengfei
Abstract: In contrast to previous approaches to chiral α‐aryl carboxylic acids that based on reactions using hazardous gases, pressurized setup and mostly noble metal catalysts, in this work, a nickel‐catalyzed general, efficient and highly enantioselective carboxylation reaction of racemic benzylic (pseudo)halides under mild conditions using atmospheric CO2 has been developed. A unique chiral 2, 2′‐bipyridine ligand named Me‐SBpy featuring compact polycyclic skeleton enabled both high reactivity and stereoselectivity. The utility of this method has been demonstrated by synthesis of various chiral α‐aryl carboxylic acids (30 examples, up to 95 % yield and 99 : 1 er), including profen family anti‐inflammatory drugs and transformations using the acids as key intermediates. Based on mechanistic experimental results, a plausible catalytic cycle involving Ni‐complex/radical equilibrium and Lewis acid‐assisted CO2 activation has been proposed. Abstract : An enantioselective carboxylation reaction using CO2 has been demonstrated as efficient for the synthesis of chiral carboxylic acids including profen family anti‐inflammatory drugs. The reaction takes place under atmospheric pressure and benefits from mild conditions using nickel‐catalysis in combination with a chiral 2, 2′‐bipyridine ligand, namely Me‐Sbpy.